The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1088/1755-1315/1134/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review and Conceptual Framework: Sustainability Construction of Implementation in Development of Special Economic Zone (SEZ) Likupang

Abstract: Likupang is one of the national tourism development areas and has been designated as a special economic zone (SEZ). It makes Likupang as the central development of infrastructure such as: Hotels, Resorts and Private Docks. In the SEZ development, several obstacles were found, including the implementation of sustainable construction regulations based on the Minister of Public Works and Public Housing Number 05/PRT/M/2015. These development activities will certainly cause problems in both economic and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Understanding the barriers can promote the development of eco-friendly, socially harmless, and economically viable strategies. This statement was also studied by several researchers; most of them found that sustainable construction will guide to a significant influence on economic factors and adequate government and reduce low investment values [4][5][6][7]. Other than that, human resources have a positive impact on sustainability after applying good government and defense culture factors.…”
Section: Introductionmentioning
confidence: 95%
“…Understanding the barriers can promote the development of eco-friendly, socially harmless, and economically viable strategies. This statement was also studied by several researchers; most of them found that sustainable construction will guide to a significant influence on economic factors and adequate government and reduce low investment values [4][5][6][7]. Other than that, human resources have a positive impact on sustainability after applying good government and defense culture factors.…”
Section: Introductionmentioning
confidence: 95%